Chronic Pelvic Pain in an Interdisciplinary Setting: 1-Year Prospective Cohort. Issue 5 (May 2018) - Allaire, Catherine; Williams, Christina; Bodmer-Roy, Sonja; Zhu, Sean; Arion, Kristina; Ambacher, Kristin; Wu, Jessica; Yosef, Ali; Wong, Fontayne; Noga, Heather; Britnell, Susannah; Yager, Holly; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2018;218:114.e1–114.e12) Chronic pelvic pain (CPP) is a common clinical problem among women. Its etiology is complex and involves an interplay of gynecologic, urologic, gastrointestinal, musculoskeletal, and psychosocial comorbidities.